Advances In Lac Insect Culture Research And Scope For Innovative Entrepreneurship Using Natural Resins And Gums - Sharma, Kewal Krishan (Indian Journal of Entomology, 2023)
Lac insects are specialized group of phytosuccivorous insects (Coccoidea: Tachardiidae) that secrete resin of industrial importance having diverse applications. Around 101 species of lac-insects and over 400 species of lac host-plants have been reported but insects belonging to sub-family Tachardiinae are considered important for laksha-culture (lac insect farming). Not only the lac insect, but also the host-plants and various biotic associations play a significant role in determining the quantity and quality of the produce. India is endowed with rich wealth of lac insect resources. 27.7% lac insect biodiversity reported from the world is found in our country under two genera i.e., Kerria and Paratachardina. Kerria the true lac secreting genus includes 28 species worldwide, 23 of which are recorded from India. Cultivation of lac / tapping of natural resins and gums not only provides livelihood to millions of lac growers but also helps in conserving the vast stretches of forests, lac insects and associated biota. Lac also provides sustained high economic returns, generates employment opportunities and has the potential to lay a strong foundation for lac based rural cottage industries. Lac farming can easily be integrated with agriculture thus helping in land use diversification for increased income. Indian Institute of Natural Resins and Gums (ICAR- IINRG) has recently developed new technologies of lac insect farming including newer host plants and developed value added products from lac and other natural resins and gums. Lac integrated farming system models and many of these products have the potential to pave the way for rural industrialization and entrepreneurship development. This review article discusses all these aspects in detail